Immune modulation promotes heart regeneration through macrophage and Granulin functions in medaka - Kaushik Chowdhury; Chia-Lin Huang; I-Ting Lin; Yu-Jen Hung; Khai Lone Lim; Hsing-Wei Liu; Ke-Hsuan Wei; Kai-Chien Yang; Yao-Ming Chang; Ben Shih-Lei Lai (Proceedings of the National Academy of Sciences, 2026)
Myocardial infarction results in irreversible cardiomyocyte loss and fibrotic remodeling in adult mammals, whereas some vertebrates retain the ability to regenerate cardiac tissue. Comparative studies suggest that immune responses critically influence repair outcomes, yet the immune programs associated with regeneration remain incompletely defined. Here, we investigate how immune modulation accelerates cardiac repair in the nonregenerative medaka ( Oryzias latipes ). Using bulk and single-cell transcriptomics combined with functional assays, we show that stimulation with the Toll-like receptor 3 agonist poly I:C accelerates early immune activation and enhances macrophage-dependent debris clearance, associated with inflammatory resolution after cardiac injury. Single-cell analysis of enriched myeloid populations identifies regeneration-associated macrophage subsets characterized by phagocytic and immune-regulatory gene programs, including elevated expression of granulin-a ( grna ). Spatial analysis by hybridization chain reaction reveals increased numbers of grna -expressing macrophages in the injury border zone, coinciding with the regenerative niche of cardiomyocyte proliferation. Consistent with these findings, administration of recombinant Granulin A enhances cardiomyocyte proliferation and reduces scar burden in medaka hearts. Together, these findings indicate that immune modulation reshapes macrophage functional states during cardiac repair and link macrophage-associated granulin expression to regenerative outcomes, highlighting macrophage properties as a potential target for improving heart repair.